Sistem Pengetahuan dan Perilaku Kesehatan di Pondok Pesantren Hidayatullah Denpasar terhadap Penyakit Scabies - Jaya, Hikmah Rian; Aliffiati, .; Sudiarna, I Gusti Putu (Sunari Penjor : Journal of Anthropology, 2022)
Scabies disease is an infectious skin disease caused by infection with the bacteria Sarcoptes scabiei. In Islamic boarding schools, students are often identified with scabies disease. This study aims to determine the knowledge system of students and caregivers about scabies disease such as views, causes, disease phases, and also the impact and health behavior. This study uses medical systems theory by Foster and Anderson and also uses qualitative research methods through data collection techniques in the form of observation, interviews, and documentation as well as using inductive data analysis techniques. Based on the results of the study, it was found that the biological impact of this disease is itching and pain experienced by the body and its social impacts such as being bullied by students who have not been infected and can also interfere with teaching and learning activities. There is an effective alternative treatment used by students and caregivers, namely the method of bathing on the beach and the compress method. Modern medicine is still used but only in a small way .